2013
DOI: 10.1080/00224499.2011.637248
|View full text |Cite
|
Sign up to set email alerts
|

Community-Engaged Research to Identify House Parent Perspectives on Support and Risk Within the House and Ball Scene

Abstract: This paper describes a community-engaged study with the Los Angeles House and Ball scene, in which the perspectives of the leaders of these communities are captured to better understand how the House and Ball communities may protect and/or increase its members’ risks for HIV infection. Data were collected through in-depth interviews with House parents (N=26). This study identified key features of both support (e.g., family and support; acceptance; validation and recognition) and risk (e.g., members’ struggle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…The majority lived together as a clan in all-hijra communities with a guru (group leader). Similar alternative family structures have been documented in the U.S. with house mothers or fathers in house and ball communities [47]. …”
Section: Opportunitiessupporting
confidence: 58%
“…The majority lived together as a clan in all-hijra communities with a guru (group leader). Similar alternative family structures have been documented in the U.S. with house mothers or fathers in house and ball communities [47]. …”
Section: Opportunitiessupporting
confidence: 58%
“…To initiate and develop a sustainable partnership with the HBC, we used the core principles of CBPR: the formation of a partnership between committed community members, organizational representatives and academic researchers which is built on trust, respect and willingness to respond to the specific health needs of the population (Craig, 2011; Kubicek et al, 2011; Rhodes, 2011) (Figure 1). CBPR also involves multidirectional exchange of information and learning, openness and trust among partners, promotion of power sharing among partners and supporting sustainability, dissemination, and/or the development of next steps in research (Rhodes et al, 2012; Rhodes, Malow, & Jolly, 2010; Salihu et al, 2011).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…This approach was chosen because it has been effective in developing and sustaining HIV prevention interventions particularly with vulnerable and marginalized populations. CBPR procedures also enable researchers to work more closely with the population of interest, thereby gaining rich insider feedback that can more accurately inform initiatives (Cashman, Eng, Siman, & Rhodes, 2011; Craig, 2011; Kubicek et al, 2011; Phillips et al, 2011; Rhodes et al, 2012). …”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has demonstrated that house parents already engage in conversations with their house children about HIV prevention and safer sex, and offer interpersonal and instrumental support (Arnold and Bailey 2009; Holloway, Traube et al 2012). House parents have also acknowledged a high level of engagement in HIV risk behaviors including escorting and other sex exchange activities, especially among young house members, in response to the pressure to purchase designer clothing, travel to out-of-town balls, and maintain their status in the ball community (Kubicek, Beyer, et al 2013). However, some house parents report not feeling comfortable or competent to counsel their house children about HIV prevention topics (Arnold and Bailey 2009; Holloway, Traube et al 2012).…”
Section: Introductionmentioning
confidence: 99%